A Possible link between Aβ42 production associated with Alzheimer's Disease and SIRT1. - Barry, Walter. (Tufts Archival Research Center, 2005)
Alzheimer's, a neurological disease commonly associated with aging, is believed to be driven by the improper clearance and thereby buildup of the 42 residue Aβ peptide. SIRT1 has a demonstrated role as a regulator of metabolism and the process of aging. Prior in virto experiments have shown a protective role of SIRT1 against neurodegenerative diseases like Alzheimer's. Here we show increased levels of SIRT1 results in decreased levels of Aβ42 peptide in the brains of a mouse model for Alzheimer's disease. These results show for the first time in vivo an inhibitory role for SIRT1 of Aβ42 production which could have important consequences for the prevention of Alzheimer's disease.